New US maritime strategy : why it matters - Till, Geoffrey (2015)
The United States has just issued a new maritime strategy. It tells a good deal about Washington's current concerns in what it calls the Indo-Asia-Pacific Region and provides an agenda to which China and other countries in the region will have to respond.